A case of Silver-Russell syndrome (SRS): multiple pituitary hormone deficiency, lack of H19 hypomethylation and favourable growth hormone (GH) treatment response - Zoran Gucev; Velibor Tasic; Jancevska, Aleksandra; Ilija Kirovski (Springer Science and Business Media LLC, 2009)
Hypomethylation of the imprinting control region 1 (ICR1) at the IGF2/H19 locus on 11p15 is linked to Silver-Russell syndrome (SRS) and/or hemihypertrophy. This SRS patient was born in term with weight of 3500 g (50 percentile) and length 48 cm (1 SD below the mean). He was first noticed at the age of 10 years for short stature (114.5 cm, -3.85 SD), relatively normal head circumference, a classic facial phenotype, hemihypertrophy (2.5 cm thinner left arm and leg in comparison to the right, asymmetric face), moderate clinodactyly and striking thinness (BMI of 15.3). At the age of 30, the body asymmetry ameliorated (1 cm thinner left arm and leg than the right), and BMI normalized (20.5 cm). Methylation analysis was performed by bisulphate treatment of DNA samples, radiolabelled PCR amplification, and digestion of the PCR products using restriction enzymes. The patient had normomethylation, and in addition hypopituitarism, with low levels of growth hormone (GH) (provocative testing before the start and after termination of GH treatment), thyroxin, TSH, FSH, LH and testosterone. The GH was given for six years, growth response was satisfactory and he reached an adult height of 166 cm. This is a first report of hypopituitarism in a patient with SRS without H19 hypomethylation. It seems that the lack of hypomethylation in this hypopituitary SRS patient is responsible, at least partly, for the favourable final adult height under GH treatment.